Web Application for Providing Score Access to Facilitating Students’ Performance - Minor , Kelvin Asclepius (Journal of Students‘ Research in Computer Science, 2023)
Promoting student engagement is a primary goal in education, and educators have identified strategies to enhance student involvement. Among these strategies, providing access to scores has emerged as a vital component. Scores, as indicators of academic performance, hold a significant influence on student participation. When students work diligently to achieve good grades or scores, they not only experience a sense of accomplishment, but the scores also fuel their enthusiasm and commitment towards their studies. Providing students with access to their scores is significant for several reasons. It fosters a positive classroom environment and positively impacts student performance. Sharing scores on Microsoft Excel in the educational system offers convenience in organizing and sharing student scores, but may lead to negative consequences, including unhealthy competition and privacy concerns. The development of web applications to provide access to students’ scores ensures improved data security and privacy through authentication measures, while also encouraging self-assessment, motivation, accountability, and communication.